Right, crime and punishment. A look from Hegel’s Philosophy of Right - Lassalle, Martina (ARFIL y UNL, 2019)
This article seeks to recover Hegel’s main contributions regarding the problem of crime and punishment in the scheme he presents in Philosophy of Right, making a continuous effort to frame them in his most general complex philosophical proposal, i.e., in the framework of the dialectical movement with which he thinks the permanent making of societies and subjects. We will mainly aim to show the way in which Hegel rejects utilitarian conceptions about punishment (prevention, dissuasion, correction) to propose an idea of punishment as retribution, but where retribution acquires a peculiar sense that, we consider, can only be read in the light of his dialectics and his singular conception of right.